A Case Study On Breast Abscess Management In Ayurveda - Yadav, Munni; Gupta, Rajesh Kumar (International Research Journal of Ayurveda & Yoga, 2021)
A breast-abscess is an accumulation of purulent substantial within the breast parenchyma that develops as a result of mastitis. As a complication, breast abscesses occur in 3-11 percent of mastitis patients, with a reported frequency of 0.1-3 percent among breastfeeding mothers. Breast-abscess is linked to Stana Vidradhi and Stana Shopha Avastha in Ayurveda (Aamavasta, Pachyamaana avasta, Pakwavasta). This research was done on a single patient. A 28-year-old married woman came in Shalya Tantra OPD , Dr.Sarvepalli Radha krishana Rajasthan Ayurveda University, Jodhpur, with a complaint of pain and abscess in her right breast for the past 2-3 months. On examination abscess was obtained in right lower outer quadrant of breast , around 4-5 cm in size. Patient was advised to use Dashaanglepa externally application followed by Jatayadi Taila externally applied. Internally Triphala Guggulu 2 tablet thrice a day with leukewarm water after food & Aragvadhadikashayam(10ml) with equal amount of water. Internal drugs were continued till the curing of wound that is up to 2weeks. Reduction of pain and healing of wound were ongoing from 4th day onwards, granulation tissue ongoing forming from 8th day onwards and mouth was closed on 12th day. Thus we can settle from the study that this Ayurveda regimen plays an actual role in management of breast- abscess.